POSTCOLONIAL PERSPECTIVES: Representations of Identity, Culture, and Power Dynamics in the Works of Salman Rushdie and Chimamanda Ngozi Adichie - Dr. Zahoor Ahmad Lone (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This paper undertakes a sustained critical examination of how Salman Rushdie and Chimamanda Ngozi Adichie negotiate the contested terrains of identity, cultural belonging, and power in their seminal works. Drawing on Rushdie's Midnight's Children (1981) and Adichie's Half of a Yellow Sun (2006) and Americanah (2013), the study argues that both writers deploy sophisticated narrative strategies — including magical realism, non-linear temporality, polyphonic narration, and metaleptic irony — to contest the epistemic violence embedded in colonial and neo-colonial discourses. The paper situates its analysis within the theoretical frameworks offered by Homi K. Bhabha's concepts of hybridity and mimicry, Gayatri Chakravorty Spivak's notion of the subaltern, Frantz Fanon's psychoanalysis of colonialism, and Stuart Hall's articulation of cultural identity. A close reading of these texts reveals that postcolonial subjectivity is neither a static residue of colonial encounter nor a transcendental essence waiting to be recovered, but rather a dynamic, contested, and perpetually re-articulated site of becoming. The paper further demonstrates that while Rushdie's literary imagination is deeply entangled with the fractured national consciousness of post-Partition India, Adichie's narrative vision is shaped by the traumatic afterlives of the Nigerian Civil War and the diasporic negotiations of Black identity in the West. Together, these authors constitute a vital cartography of postcolonial writing in which the personal and the political are shown to be inseparable.